High TSH levels during TSH suppression therapy in DTC postoperative patients are associated with low DIO2 expression in the thyroid and impaired thyroid hormone sensitivity - Wu, Jialu; Huang, Juan; Yan, Zhe; Yuan, Anqi; Song, Yifei; Huang, Hui (Frontiers in Endocrinology, 2025)
IntroductionSome patients with differentiated thyroid cancer (DTC) exhibit persistently elevated TSH levels despite undergoing TSH suppression therapy after total thyroidectomy. This study aims to investigate the expression of type 2 deiodinase (DIO2) in thyroid tissues, as well as central and peripheral thyroid hormone sensitivity in these patients.MethodsA total of 162 DTC patients who underwent total thyroidectomy and received TSH suppression therapy were enrolled. Patients were stratified into Low TSH and High TSH groups based on postoperative TSH levels. Thyroid function and thyroid hormone sensitivity indices were compared before and after treatment, and DIO2 expression in normal thyroid tissue was analyzed.ResultsAll patients showed significantly elevated FT4 levels after TSH suppression therapy. Postoperative FT3 levels in the High TSH group were lower than preoperative levels. Notably, the High TSH group exhibited significantly lower FT3/FT4 ratios and higher central thyroid sensitivity indices than the Low TSH group. Immunohistochemistry revealed reduced DIO2 expression in thyroid tissues of the High TSH group. This significant difference persisted when analysis was restricted to patients with normal FT4 levels in both groups. DiscussionDTC patients with persistently high postoperative TSH levels display lower DIO2 expression in normal thyroid tissues. These findings suggest that poor responders to TSH suppression therapy inherently exhibit impaired central and peripheral thyroid hormone sensitivity, which may be exacerbated by total thyroidectomy. TSH index shows predictive value for L-T4 monotherapy efficacy. These results highlight the need for personalized TSH suppression strategies in DTC management.